English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can you help me with this because the example in my book is not clear

2007-03-09 00:32:44 · 13 answers · asked by jardale 1 in Science & Mathematics Mathematics

13 answers

7(x-2)+13=3(x+5)
7x-14+13=3x+15
7x-3x=15+14-13.
4x=16
x=4

2007-03-09 00:41:52 · answer #1 · answered by Anonymous · 0 0

7(x - 2) + 13 = 3(x + 5)
> 7x - 14 + 13 = 3x + 15
> 7x - 1 = 3x + 15
> 7x - 3x = 15 +1
> 4x = 16
> x = 16/4
> x = 4

2007-03-09 08:39:06 · answer #2 · answered by ganesan 2 · 0 0

You multiply the 7 x the (x-2), and then the 3 x the (x+5), which brings you to, 7x-14+13=3x+15. Then you subtract 13 from both sides, which leaves you with, 7x-14=3x+2. Then you want to get all the x's on one side, so you would subtract 3x from both sides, leaving you with, 4x-14=2. Now you want to have the x's on one side and the numbers without the x's on the other, so you would add 14 to both sides, which would leave you with, 4x=16. Finally, you divide both sides by 4, leaving you with x=4.

2007-03-09 08:47:31 · answer #3 · answered by Anonymous · 0 0

7(x-2) + 13 = 3(x+5)
7x - 14 +13 = 3x + 15
7x - 3x = 15 + 14 - 13
4x = 16
x = 16/4
x = 4

enjoy your study

2007-03-09 08:42:27 · answer #4 · answered by tooon68 3 · 0 0

7(x-2)+13=3(x+5)

=> 7x-14+13=3x+15

=> 7x-1=3x+15

=>7x-3x=15+1

=>4x=16

=>x=16/4

=>x=4. (solved)

2007-03-09 08:46:33 · answer #5 · answered by cosmos 2 · 0 0

7(x - 2) + 13 = 3(x + 5)

First, expand both sides by distributing each number over the brackets.

7x - 14 + 13 = 3x + 15

Now, move all terms with x in them to the left hand side, and everything else to the right hand side.

7x - 3x = 14 - 13 + 15

Group like terms.

4x = 16

Divide both sides by 4.

x = 4

2007-03-09 08:38:52 · answer #6 · answered by Puggy 7 · 0 0

first a number outside the bracket means multiplication. So 7*x= 7x. + and - results in -. Therefore 7x-14+13=3x+15. bring the like terms to one side of the equal to sign: 7x-3x(when a number shifts its place from one side of the equal to sign to another, its sign changes opposite. hence +3 changes to -3). So 7x-3x=15+14-13.
4x=29-13.
4x=16
x=16/4(since 4x means 4*x and then shifts places)
x=4

2007-03-09 09:45:53 · answer #7 · answered by cute little 1 · 0 0

7(x-2)+13=3(x+5)

7 x (x-2)+13= 3 x (X+5)
7x-14+13= 3x + 15
7x-1= 3x + 15
4x = 16
x= 4

This is what I think the answer is.

2007-03-09 08:39:19 · answer #8 · answered by Anonymous · 0 0

Multiply each of the things in the brackets by the number in front of the brackets. So for example:

7(x-2) become 7x - 14

Then subtract 3x from both sides of the equation. This moves all the x's to one side. Finally add 1 to both sides of the equation which moves all the numbers which don't have an x to the one side.

2007-03-09 08:38:16 · answer #9 · answered by Gnomon 6 · 0 0

it must be like this..
7(x-2)+13=3(x+5)
7x-14+13=3x+15
7x-3x=15+14-13
4x=16
x=4..

i'm so pleased if i find this quest in my test paper =p

2007-03-09 08:40:27 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers